The “soy-ization” of Argentina: The dynamics of the “globalized” privatization regime in a peripheral context - Delvenne, Pierre (2013)
Based on extensive fieldwork conducted with actors from public, private and associative sectors, we explore the expansion of genetically modified soy in Argentina and we aim to figure out how the neoliberal “globalized privatization regime” unfolded in a peripheral location. Our case points at two inherent contradictions with such a regime's main tenets, namely that it needs a weak antitrust policy (thus leading to a market situation dominated by a monopoly of transnational companies) and a hyper-restrictive system of intellectual property. We highlight the participation of two groups of local actors in the regime. The first group is aligned with the globalized privatization regime agendas, while the second is involved in protest and regulatory actions focusing on the health, environment and safety issues related to the GM soy complex. To a different extent, both groups share a local agenda of resistance and an anti-imperialist imaginary. Both have national development objectives of Argentina in their ideological roots, although their conceptions of “development” are different (industrial development vs. protection of peasants' life and the environment). We conclude that it is not enough to postulate that the neoliberal globalized privatization regime will just expand to the South as it did in Northern countries. Rather, combined with the commercialization of science, peripherality creates protest, activism and local regulation.